Challenges Surrounding the Diagnosis of Autism in Children - Hus, Yvette; Segal, Osnat (My University, 2021)
This comprehensive thematic review aims to highlight and familiarize readers with the challenges and pitfalls encountered in differential diagnosis of autism spectrum disorders (ASD) in children to facilitate the process of accurate identification by stakeholders. Accordingly, articles that best answer our questions and highlight our concerns were chosen from well-established publishers with prime peer reviewed journals. Included are studies showing alternate views of the issues so as to point readers to other possibilities. ASD, a complex dynamic biological-neurodevelopmental disorder, is underscored by its heterogeneous symptomology, severity, and phenotypes - all characterized by social communication deficits and presence of restricted interests and repetitive behaviours (RRBs), the core symptoms in ASD. Language and intellectual capacities do not form ASD core symptoms although vary considerably. Accurate identification is challenging as ASD is often enmeshed with other neurodevelopmental disorders, and medical comorbidities, a situation now recognized as the rule rather than the exception in child psychiatry and developmental medicine. ASD is a disorder with varying performance and severity of symptoms over time, including unexpected loss of early skills, and lost diagnosis in some children following treatment. The review reiterates the urgency in accurate diagnosis in face of the rapid rise in ASD prevalence globally, and risk-increase in delayed or denied treatment with undesirable life-long consequences for most of the affected children. In addition, a call for change is advised to circumvent the ethical dilemma posed by the present "deficit model" in ASD diagnosis. Here, ASD prevalence is presented first, followed by emphasis on importance of accurate early diagnosis, and challenges in its accomplishment due to flaws in diagnostic instruments and other contributing factors. Next follow the required criteria for accurate identification, and its difficulties attributed to comorbid conditions, gender differences, and socio-economic and cultural influences. The conclusion includes future directions and a take away message.
Keywords: Autism; Comorbidities; Missed and misdiagnosis; Neurodevelopmental disorders